Health-care reform in Turkey: far from perfect - Atun, Rıfat; Aydın, Sabahattin; Aran, Meltem; Gürol, İpek; Chakraborty, Sarbani; Akdağ, Recep (Elsevier, 2014)
In analysing the eff ects of the Turkish health reforms, we were careful to use reliable data from the Turkish Demographic and Health Survey (TDHS) 1993, 1998, 2003, and 2008; the Turkish Household and Budget Surveys (THBS) 2003–11 done annually by the Turkish Statistical Institution; and the health expenditure and health insurance coverage data from the Social Security Institution
WOS: 000329341200001
PubMed ID: 24388314